Adaptive Frequency Evaluation Method - Lukocius, R.; Virbalis, J. A. (Elektronika ir Elektrotechnika, 2011)
Frequency evaluation of the periodical signal which is affected by noise is common problem in a variety of the systems. Low frequency noise often could be very big in comparison to useful signal. Application of the infinity impulse response filters could be unacceptable in some cases because of the filters induced ripples. High order finite impulse filters are needed for sufficient suppression. Furthermore power consumption is important factor for portable battery powered devices. There is presented frequency evaluation method based on adaptive relatively wide difference window application for peaks detection and on amplitude evaluation. The method could be easy implemented in fixed point arithmetic.